2018
DOI: 10.1002/adfm.201704434
|View full text |Cite
|
Sign up to set email alerts
|

Optomagnetic Nanoplatforms for In Situ Controlled Hyperthermia

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 67 publications
(6 reference statements)
2
54
0
Order By: Relevance
“…Recently, Ortegies et al [176] reported the realization of an optomagnetic nanoplatforms which is able to generate heat using MHT and to emit in the NIR to allow the detection of the particles and a direct measurement of the progress of the heating process. The thermal control on the MHT process was achieved doping Nd SPION particles with LaF 3 which is luminescent in temperature range of 20-60 °C.…”
Section: Comparison Between Magnetic and Photo-mentioning
confidence: 99%
“…Recently, Ortegies et al [176] reported the realization of an optomagnetic nanoplatforms which is able to generate heat using MHT and to emit in the NIR to allow the detection of the particles and a direct measurement of the progress of the heating process. The thermal control on the MHT process was achieved doping Nd SPION particles with LaF 3 which is luminescent in temperature range of 20-60 °C.…”
Section: Comparison Between Magnetic and Photo-mentioning
confidence: 99%
“…The calibration law ∆(2θ) = 2θ − 2θ 0 = f(∆T) of each plane is presented in Figure 4. The 2θ position of each peak is determined from a fit with a gaussian function and is related to the lattice parameter via equation (1). The error bars on the heating T are obtained from 170 the covariance matrix of the least squares gaussian fit function.…”
Section: The Evolution Of the Diffraction Pattern In The Temperaturementioning
confidence: 99%
“…The fact that magnetic nanoparticles (MNPs) generate heat when they are excited by a high-frequency magnetic field permits various potential applications like tumor therapy 1 , catalysis 2 or water electrolysis 3 . This diversification has been made possible thanks to continued progresses in the fabrication of chemically-synthesized MNPs, improving the control over their size, shape (core-shell structure, surface morphology), chemical composition and heating power 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic hyperthermia has been applied in the field of cancer therapy, [17][18][19][20] but it has been shown recently that the same principle can also be advantageously applied in heterogeneous catalysis. [21][22][23][24][25][26][27][28][29] The concept is based on the fact that ferromagnetic materials placed in a highfrequency alternating magnetic field release heat through hysteresis losses.…”
Section: Introductionmentioning
confidence: 99%